Resistance to antibiotics and presence of plasmid in enterobacteria and staphylococcus aureus in the sector of diet of a public hospital - Cardoso Lisboa Pereira, Simone; Silva Ribeiro, Roberta; Soares Bazzolli, Denise Mara; Dantas Vanetti, Maria Cristina (O Mundo da Saúde, 2015)
The occurrence of antibiotic-resistant bacteria has become more frequent and the presence of these microorganisms in hospitals exposes patients to serious risks. The presence of enterobacteria resistant to antibiotics and the presence of plasmid DNA in the isolates were evaluated in a sector of dietary action a Brazilian public hospital. The enumeration and isolation of enterobacteria were done in samples collected from food handlers, utensils, and food processing surfaces. Biochemical identification of the isolates was done, and serum confirmations as well when necessary. The susceptibility to antibiotics of therapeutic use was determined by the diffusion technique in agar and plasmidial DNA detection was done by agarose gel electrophoresis. Fourteen genera and 27 species of enterobacteria and others Gram negative bacteria were identified out of 150 isolates obtained. Seventy-four isolates (58%) presented resistance to antibiotics. Seventy-four percent of the antibiotic resistant isolates had palsmidial DNA. There was a significant difference between isolates resistant to ampicillin (p=0.00) and kanamycin (p=0.03) in relation to sources of the samples. The presence of plasmidial DNA was more prevalence in isolates resistant to antibiotics, but it was found that this correlation was significant only for the antibiotic tetracycline. These results show how important aspects of the risk of propagation of antibiotic resistant bacteria, the majority of plasmid DNA carrier, for processed foods in this environment and may result in hospital infections and contribute to the failure of antimicrobial therapies.